Perancanaan Strategis SI/TI Menggunakan Framework Ward and Peppard Pada Sekolah Kristen - Triady, Sevilla; Andry, Johanes Fernandes (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
The application of information technology and information systems is currently a much-needed factor in organizations. The development of information technology as part of IS and science has influenced many fields, one of which is the sectors of education, namely schools. Christian schools are educational organizations whose learning processes teach based on the Bible. Christian schools have used several IT developments in their business processes. However, the use of this technology is not optimal. This research will carry out the strategic design of information systems using the Ward and Peppard framework with supporting analysis such as value chain, SWOT, CSF, and McFarlan’s Strategic Grid. This framework can help organizations analyze business and technology from the internal and external sides of the organization. This research was conducted to align business processes by making maximum use of IS/IT. The final result of the research is a proposed application that is tailored to the business processes and business needs of Christian schools which is expected to be able to align their business processes and achieve business goals.